Reorienting retirement risk management - Clark, Robert L. (Robert Louis), 1949-; Mitchell, Olivia S. (Oxford : Oxford University Press, 2010)
This volume explores how workers and firms should reassess the risks associated with retirement saving and dissaving to identify creative ways to enhance retirement risk management. It examines the key role for financial literacy and education programs, better pension design and innovative financial products in addressing new economic realities.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Retirement -- Planning; Financial risk management